Reliability-based design of rockfall passive systems height. (March 2021) - Marchelli, Maddalena; De Biagi, Valerio; Peila, Daniele
Abstract: Passive structural systems against rockfalls, as net fences and embankments, are among the most effective mitigation measures for high energy events. Although largely adopted, the design of these systems has not been codified yet. A profitable time-dependent reliability approach has been recently introduced by the Authors, accounting for different possible probability distributions of velocity, mass, and height of the impacting block. Two failure modes were considered, related to the energy absorption capacity and the intercepting height of the systems. As the current design approach is based on partial safety factors, several sensitivity analyses are herein presented, with a particular focus on the height, firstly to define a suitable combination of equivalent partial safety factors, and, secondly, to investigate the parameters related to the geometry and the kinematics of the block which mostly affect the factors. Moreover, for a given failure probability, two shallow neural network were built, one for each failure mode, considering the possible range of all the input parameters, creating thus two input-output relationships that can be used to evaluate the partial safety factors for the height and the energy.